Tailoring the Magnetic Properties of Ni81fe19 Thin Films by Varying Their Thickness - Escrig-Murua, J; Alburquenque-Munoz, D; Alburquenque-Munoz, D (Elsevier B.V., 2017)
Ni81Fe19Oy thin films with different thicknesses were obtained by atomic layer deposition. After a thermal reduction process, Ni81Fe19Oy films were converted to their strong Ni81Fe19 ferromagnetic phase, usually known as Permalloy. The different thicknesses were obtained by considering 500, 1000, 1500 and 2000 supercycles, which are defined as a cycle of NiCp2/O3 followed by another cycle of FeCp2/O3. The samples were characterized before and after the thermal reduction process with respect to their crystallinity, morphology and magnetism. In particular, the thermally reduced samples exhibit holes whose sizes increase significantly as the thickness of the samples also increases, affecting their magnetic behaviour. As Permalloy is widely used in many applications, its synthesis through atomic layer deposition is expected to introduce comparative advantages over other synthesis processes, opening up new possibilities for nanoelectronic devices. © 2017 Elsevier B.V.